First reported case of afatinib‐associated toxic megacolon. Issue 7 (31st August 2018) - Kwok, Wang Chun; Tam, Terence Chi Chun; Lam, David Chi Leung
Abstract : We report the first case of toxic megacolon associated with afatinib use, which is a potentially fatal complication, with risks of colonic perforation. In this case, the condition improved on stopping afatnib. Clinicians need to be alert of this rare but fatal adverse effect and to avoid anti‐diarrhoeal agents, which can worsen toxic megacolon. Anti‐diarrhoeal agents are routinely given if diarrhoea occurs on afatinib. These should be stopped and avoided if toxic megacolon occurs. Abstract : We report the first case of toxic megacolon associated with afatinib use, which is a potentially fatal complication, with risks of colonic perforation. In this case, the condition improved on stopping afatnib. Clinicians need to be alert of this rare but fatal adverse effect and to avoid anti‐diarrhoeal agents, which can worsen toxic megacolon.